Fungsi Pengawasan Dewan Pendidikan Provinsi Sumatera Barat Dan Implikasinya Dalam Proses Penerimaan Peserta Didik Berbasis Zonasi Tingkat SMA Di Provinsi Sumatera Barat Tahun 2022 - Harry Febri; Erwin; Ira Wahyuni (Jurnal Niara, 2024)
This study aims to examine the role and function of the Board of Education in improving the quality of education in West Sumatra Province. The focus in this research is how the supervisory function of the Board of Education and its implications in the process of New Student Admissions based on high school level zoning in West Sumatra Province in 2022. The approach used in this research is a descriptive approach with a qualitative type. Data collection procedures used are observation, interviews, documentation. The subjects in this study consisted of various sources (Chair of the Education Council, Members of the Education Council, Secretary of the Education Office, Head of PSMA, Head of GTK, School Principal, Functional Planning Bappeda). Data analysis was carried out interactively and continuously. The results of the study show that the role of the Board of Education in improving the quality of education in West Sumatra Province is still not optimal, then the role of the Board of Education as supervisors has not gone well. The results of the study can be concluded that the supervisory function of the Board of Education and its implications in the zoning-based zoning process for New Students in West Sumatra Province in 2022 has not been optimally implemented